2018
DOI: 10.1029/2018jc014168
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Three Atlantic Branches Entering the Arctic Ocean With 129I and 236U

Abstract: This study presents the data on 129 I and 236 U concentrations in seawater samples and sea ice cores obtained during two expeditions to the Arctic Ocean that took place onboard R/V Polarstern (PS94) and R/V Lance (N-ICE2015) in summer 2015. Carbon-14 was also measured in the deep water samples from the Nansen, Amundsen, and Makarov Basins. The main goal was to investigate the distribution of 129 I and 236 U in a transect from the Norwegian Coast to the Makarov Basin to fully exploit the potential of combining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(108 citation statements)
references
References 43 publications
4
103
0
1
Order By: Relevance
“…The residence time of deep water in the Makarov Basin was determined to be 400–650 years based on the 226 Ra profile at station 30 (Figure S10) and the range in the 226 Ra flux from sediments in the Makarov Basin. This value is similar to previous estimates of ~300–600 years (Jones et al, ; Schlosser et al, ; Tanhua et al, ; Casacuberta et al, ; Rutgers van der Loeff et al, ). The deep waters at stations 48, 52, and 57 in the deep Canada Basin (Figure S10) were determined to have residence times of 130–270 years based on the range of 226 Ra fluxes estimated for sediments in both the Makarov and Canada Basins.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The residence time of deep water in the Makarov Basin was determined to be 400–650 years based on the 226 Ra profile at station 30 (Figure S10) and the range in the 226 Ra flux from sediments in the Makarov Basin. This value is similar to previous estimates of ~300–600 years (Jones et al, ; Schlosser et al, ; Tanhua et al, ; Casacuberta et al, ; Rutgers van der Loeff et al, ). The deep waters at stations 48, 52, and 57 in the deep Canada Basin (Figure S10) were determined to have residence times of 130–270 years based on the range of 226 Ra fluxes estimated for sediments in both the Makarov and Canada Basins.…”
Section: Discussionsupporting
confidence: 91%
“…Intermediate waters move cyclonically around the Arctic; one pathway follows the Eurasian side of the Lomonosov Ridge and another crosses the Lomonosov to enter the Makarov and Canada Basins (Rudels et al, ; Schauer et al, ; Smethie et al, ). Anthropogenically sourced tracers such as 3 H, SF 6 , 129 I, and 236 U have been used to denote recent ventilation of intermediate water in the Amundsen, Canada, and Makarov Basins and indicate that the residence time of this water mass is on the order of decades (Casacuberta et al, ; Ekwurzel et al, ; Rutgers van der Loeff et al, ; Schlosser et al, ; Smethie et al, ; Smith et al, ; Smethie & Swift, ; Tanhua et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet a recent study (Casacuberta et al, ) found that the 129 I and 236 U signals from LH and SF do not completely mix in the North Sea, suggesting three different input functions for Atlantic waters entering the Arctic Ocean (two branches entering via Barents Sea, green and purple in Figure a and one via Fram Strait, orange in Figure a). The high 129 I/ 236 U ratio released from LH largely remains within the NCC, which enters the Barents Sea very close to the Norwegian coast.…”
Section: Discussionmentioning
confidence: 91%
“…Apart from the temporal variation of 129 I/ 236 U from RP, the combination of 129 I and 236 U allows distinguishing between the two main anthropogenic sources (i.e., RP and GF), as they are characterized by very different 129 I and 236 U concentrations as well as 129 I/ 236 U atom ratios (Casacuberta et al, , ). To this purpose, the dual‐tracer approach of using the 236 U/ 238 U ratio together with the 129 I/ 236 U ratio has been suggested and used to constrain sources of water masses (Christl, Casacuberta, Vockenhuber, et al, ; Casacuberta et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation